Profil Kromatografi Senyawa Aktif Antioksidan dan Antibakteri Fraksi N-Heksana Daun Libo (Ficus variegata Blume) - Rolan Rusli; Myra Puspha Hardina; Fairul Muflihah; Agung Rahmadani (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2015)
Research about chromatographic profile of antioxidant and antibacterial compounds in n-hexane fraction of Libo leaves (Ficus variegata Blume.) has been done in order to know the form of chromatographic profile of antioxidant and antibacterial compounds in n-hexane fraction of Libo leaves. Extraction was done by maceration using methanol. Isolation was done by 2 methods, vacuum liquid chromatography (VLC) then followed by conventional column chromatography. Eluent used are n-hexane-ethyl acetate and methanol-chloroform. The results based on conventional column chromatography are as many as 10 fractions. The fractions are being conducted then by a qualitative testing of the antioxidant activity using DPPH method and antibacterial activity test using bioautography TLC method. The results formed as a chromatographic profile of fraction that contain antioxidant and antibacterial activity, which are as many as 5 fractions (NHB1, NHB3, NHB4, NHC1, NHC3) active as an antioxidant and 4 fractions (NHB1, NHC1, NHC2, NHC3) which are active as an antibacterial. The secondary metabolite contents of the fractions are alkaloid, flavonoid and steroid/terpenoid.